Corporate Governance Practices and Their Contribution to Achieving Saudi Arabia’s Vision 2030 Objectives: An Applied Study on Emerging Cybersecurity Companies - Alduriweesh, Mohammad Abdulaziz (Journal of Economic, Administrative and Legal Sciences, 2025)
This study seeks to analyze corporate governance practices in emerging cybersecurity companies and their role in achieving the objectives of Saudi Arabia’s Vision 2030, in light of digital transformation and regulatory reforms aimed at enhancing transparency and investor confidence. The significance of the study lies in enriching the theoretical literature on corporate governance and providing an applied framework that promotes transparency, organizational flexibility, and the development of a secure digital society, thereby strengthening investor trust and contributing to the sustainability of the digital economy. The findings reveal a statistically significant relationship between the level of governance practices implemented in emerging cybersecurity companies and their ability to support Vision 2030 objectives, as well as statistically significant differences in governance evaluations attributable to practitioners’ characteristics (such as gender and job position within the cybersecurity sector). The study further emphasizes that adopting proposals to enhance governance practices contributes to improving organizational efficiency and sustainability in line with national goals. It recommends reinforcing the commitment of cybersecurity companies to applying governance principles as a pathway to achieving Vision 2030, activating the role of boards of directors by engaging specialized expertise, developing flexible regulatory frameworks tailored to the nature of emerging firms, and adopting performance indicators to measure transparency and compliance. Ultimately, the study concludes that governance should be viewed not merely as a legal requirement, but as a cornerstone for sustainable growth and the advancement of the national digital economy.